Enhancing Visualization of Gold Markers in Prostate Cancer Radiation Therapy Planning Through MRI Pulse Sequence Optimization (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Prostate cancer treatment often involves the use of gold markers to enhance the accuracy of radiation therapy. However, the visualization of these markers using MRI remains a challenge due to their small size and susceptibility to artifacts. This study investigates the optimization of MRI pulse sequences to improve the visibility of gold markers in the context of radiation therapy simulation for prostate cancer patients. By comparing various pulse sequences and their parameters, we aim to identify the optimal configuration that provides the best contrast and minimal artifacts.